2014
DOI: 10.1007/s13277-014-2728-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum vitamin D level on risk of bladder cancer: a systemic review and meta-analysis

Abstract: Vitamin D has important biological functions including modulation of the immune system and anti-cancer effects. There was no conclusive finding of the impact of serum vitamin D level on bladder cancer risk. A systemic review and meta-analysis was performed to assess the impact of serum 25-hydroxyvitamin D level on bladder cancer risk. The pooled relative risk (RR) with 95% confidence interval (95%CI) was used to assess the impact of serum 25-hydroxyvitamin D level on bladder cancer risk. A total of 89,610 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…The MA by Liao et al [39] investigated only the role of vitamin D serum level. They found that the risk of bladder cancer was decreased among individuals with the highest levels of serum vitamin D (RR 0.75; 95 % CI 0.65–0.87; n = 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MA by Liao et al [39] investigated only the role of vitamin D serum level. They found that the risk of bladder cancer was decreased among individuals with the highest levels of serum vitamin D (RR 0.75; 95 % CI 0.65–0.87; n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…smokingI 2  = 0 %Supplementation versus placebo or no supplementationYesRRms = 0.64; 95 % CI 0.47–0.82Most adjusted, incl. smokingI 2  = 0 %Jeon et al [37]Beta-carotene supplements2 RCTSupplementation versus placebo or no supplementationNoRR 1.52; 95 % CI 1.03–2.242I 2  = 0.0 %Liao et al [39]Vitamin D1 CC2 NCC2 COHSerum levels; high versus lowYesRRs = 0.75; 95 % CI 0.65–0.875SmokingI 2  = 0.0 %Egger p  = 0.57Chen et al [40]Vitamin D1 CC3 COHCirculating levels; high versus lowNoRR 0.75; 95 % CI 0.57–0.994I 2  = 51.7 %Egger p  = 0.873 studiesDiet and supplement; high versus lowNoRR 0.92; 95 % CI 0.66–1.283I 2  = 32.3 %Egger p  = 0.41Vitamin E4 CC5 COHDiet; high versus lowNoRRm = 0.69; 95 % CI 0.52–0.925I 2  = 47.1 %Egger p  = 0.013 CC3 COHDiet and supplement; high versus lowNoRRm = 0.76; 95 % CI 0.56–1.025I 2  = 49.8 %Egger p  = 0.35…”
Section: Appendixmentioning
confidence: 99%
“…Different meta-analysis have linked a higher risk of cancer with lower vitamin D levels, Ma et al [42] analysed nine studies with over 1 million participants demonstrating an inverse relationship between vitamin D intake and blood serum levels with colorectal cancer risk and Liao et al [43] showed that individuals with higher vitamin D serum levels had a lower risk to develop bladder cancer. There is also evidence for breast cancer, a dose response meta-analysis carried out by Bauer et al [44] showed a nonlinear inverse association between circulating vitamin D levels and breast cancer risk for postmenopausal women, a flat association was found for levels <27 ng/ml (67.5 nmol/l), while breast cancer risk decreased for higher concentrations between 27 and 35 ng/ml (67.5-87.5 nmol/l) with a 5 ng/ml (12.5 nmol/l) increase associated to a 12% lower risk of breast cancer.…”
Section: Cancer Risk and Prognosismentioning
confidence: 99%
“…High serum 25(OH)D levels were found to significantly decrease the risk of bladder cancer (SRR: 0.75; 95%CI: 0.65-0.87) in a recent meta-analysis (Liao, Huang, Qiu, & Ma, 2015), while no association between 25(OH)D and ovarian cancer risk was suggested by meta-analysis of 10 studies (Yin et al, 2011).…”
Section: (Oh)d and Cancer Riskmentioning
confidence: 93%